2015
DOI: 10.5935/0004-2749.20150058
|View full text |Cite
|
Sign up to set email alerts
|

Vision-related quality of life in children with retinopathy of prematurity

Abstract: Purpose: To evaluate the effect of retinopathy of prematurity (ROP) on vision-related quality of life in children. Methods: The Children's Visual Function Questionnaire (CVFQ), an instrument that evaluates vision-related quality of life in children, was used. It is divided into 6 subscales: General Health, Vision Health, Competence, Personality, Family Impact, and Treatment. The sample consisted of parents of premature children up to 3 years of age who had ROP and no neurological damage (ROP group) and parents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
15
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 22 publications
8
15
0
3
Order By: Relevance
“…; Messa et al. ). In our study, 35% of preterm children had VA of 20/40 Snellen (0.3 logMAR) or less, which, if stable through adulthood, might preclude that person from obtaining a driving licence (dependent on the law in each country) or might impair other life activities.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…; Messa et al. ). In our study, 35% of preterm children had VA of 20/40 Snellen (0.3 logMAR) or less, which, if stable through adulthood, might preclude that person from obtaining a driving licence (dependent on the law in each country) or might impair other life activities.…”
Section: Discussionmentioning
confidence: 97%
“…It has been suggested that the foveal changes at the critical time of fovealization in premature infants may impair their VA in the adult life (Vinekar et al 2011), thus lowering their quality of life (Dunbar et al 2009;Messa et al 2015). In our study, 35% of preterm children had VA of 20/ 40 Snellen (0.3 logMAR) or less, which, if stable through adulthood, might preclude that person from obtaining a driving licence (dependent on the law in each country) or might impair other life activities.…”
Section: Bcva Logmarmentioning
confidence: 99%
“…As limitações visuais da criança foram sentidas com tristeza; quanto mais a criança se afasta da condição de normalidade, ou seja, quanto mais grave a doença e suas sequelas, maiores as dificuldades de participação social e convívio familiar. Tal situação se relaciona aos dados de estudos que apontam o impacto da qualidade de vida com a gravidade da doença ocular (Birch, Cheng, & Felius, 2007;Messa, Mattos, Areco, & Sallum, 2015). De acordo com Holditch-Davis et al (2009), a aparência do prematuro mobiliza os pais, que podem apresentar dificuldades em lidar com posicionamento social da criança e o estranhamento das pessoas (Souza et al, 2010).…”
Section: Discussionunclassified
“…Estudos apontam o impacto negativo ocasionado pela doença ocular na qualidade de vida das famílias de bebês prematuros com ROP. Quanto mais grave a doença, pior a qualidade de vida (Birch, Cheng, & Felius, 2007;Messa, Mattos, Areco, & Sallum, 2015).…”
unclassified
“…Till date the quality of life in ROP babies and the social impact of the disease on life of the child and their families have been an ignored aspect of the management and literature on the topic is scant. [56] The Western population data may also not be valid for developing countries due to gross social, cultural, and economic differences. In this study, we evaluated the impact of treated ROP on quality of life of affected children and their families.…”
mentioning
confidence: 99%